Case study: Evaluating deep-water start techniques and training demands in seated slalom waterskiing for an athlete with paraplegia - Suárez-Iglesias, David; Ayán, Carlos; García-Fresneda, Adrián; Villa-Vicente, José Gerardo; Rodríguez-Medina, Juan; Rodríguez-Marroyo, Jose A. (Frontiers in Psychology, 2024)
Purpose: Recreational and competitive slalom waterskiing is increasingly popular among individuals with spinal cord injuries (SCI), particularly for those with paraplegia using sit-skis. A key component of slalom skiing is the deep-water start (DWS), yet little is known about the physiological and physical demands of this activity when the athlete isin a seated slalom context. This study aims to fill this gap by focusing on the training requirements for adaptive a seated slalom skiersathlete.Focusing on a young male skier athlete with paraplegia, this case study evaluates the effectiveness and efficiency of traditional (TDWS) and alternative (ADWS) DWS techniques during seated slalom waterskiing sessions. It assesses internal training load (TL) through heart rate (HR) zones and session-rated rating of perceived exertion (sRPE), alongside pre-and postpractice session handgrip strength measurements to gauge peripheral muscle fatigue.Performing the ADWS, achieving a full success rate, proved more effective but slightly more time-consuming than TDWS, which had limited success. HR during DWS maneuvers ranged from 63.2% to 81.3% of maximal HR, with most sessions occurring below the ventilatory threshold, thus perceived as hard effort. A moderate yet non-significant correlation was found between HR and sRPE-based TL. A significant reduction in handgrip strength post-training session underscores the discipline's activity's demands. These insights illuminate the technical, physiological, and physical challenges in mastering DWS for skiers seated slalom athletes with SCI, providing valuable guidance for the development of tailored training programs and techniques in seated slalom waterskiingthis sport.